Neonatal brain-directed gene therapy rescues a mouse model of neurodegenerative CLN6 Batten disease. (6th September 2019) - kleine Holthaus, Sophia-Martha; Herranz-Martin, Saul; Massaro, Giulia; Aristorena, Mikel; Hoke, Justin; Hughes, Michael P; Maswood, Ryea; Semenyuk, Olha; Basche, Mark; Shah, Amna Z; Klaska, Izabela P; Smith, Alexander J; et al.
Abstract: The neuronal ceroid lipofuscinoses (NCLs), more commonly referred to as Batten disease, are a group of inherited lysosomal storage disorders that present with neurodegeneration, loss of vision and premature death. There are at least 13 genetically distinct forms of NCL. Enzyme replacement therapies and pre-clinical studies on gene supplementation have shown promising results for NCLs caused by lysosomal enzyme deficiencies. The development of gene therapies targeting the brain for NCLs caused by defects in transmembrane proteins has been more challenging and only limited therapeutic effects in animal models have been achieved so far. Here, we describe the development of an adeno-associated virus (AAV)-mediated gene therapy to treat the neurodegeneration in a mouse model of CLN6 disease, a form of NCL with a deficiency in the membrane-bound protein CLN6. We show that neonatal bilateral intracerebroventricular injections with AAV9 carrying CLN6 increase lifespan by more than 90%, maintain motor skills and motor coordination and reduce neuropathological hallmarks of Cln6 -deficient mice up to 23 months post vector administration. These data demonstrate that brain-directed gene therapy is a valid strategy to treat the neurodegeneration of CLN6 disease and may be applied to other forms of NCL caused by transmembrane protein deficiencies in the future.